Update of the search for the neutrinoless decay tau ->mu gamma - Ahmed, S; Alam, MS; Athar, S; Jian, L; Ling, L; Mahmood, A; Saleem, M; Timm, S; Wappler, F; Anastassov, A; Duboscq, J; Gan, K; et al. (2000)
We present an update of the search for the lepton family number violating decay τ→μγ using 12.6 million τ+τ- pairs collected with the CLEO detector. No evidence of a signal has been found and the corresponding upper limit is script B sign(τ→μγ)<1.1×10-6 at 90% C.L., significantly smaller than previous experimental limits. ©2000 The American Physical Society.